2016
DOI: 10.2196/rehab.4511
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of a Smartphone to Measure Standing Balance

Abstract: BackgroundBalance assessment and training is utilized by clinicians and their patients to measure and improve balance. There is, however, little consistency in terms of how clinicians, researchers, and patients measure standing balance. Utilizing the inherent sensors in every smartphone, a mobile application was developed to provide a method of objectively measuring standing balance.ObjectiveWe aimed to determine if a mobile phone application, which utilizes the phone’s accelerometer, can quantify standing bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…These findings are in line with previously published work which has demonstrated that males possess poorer PC than females, while PC improves with the transition from youth to young adulthood [74]. A further nine studies compared PC performance during different static stance conditions [29,32,41,43,44,[46][47][48]75]. Two studies failed to quantitatively compare conditions [32,43], while the seven remaining studies demonstrated significant differences between conditions, with more challenging stances causing increased instability [25,29,41,44,46,48,76].…”
Section: Discriminant Validity -Healthy Populationssupporting
confidence: 87%
See 4 more Smart Citations
“…These findings are in line with previously published work which has demonstrated that males possess poorer PC than females, while PC improves with the transition from youth to young adulthood [74]. A further nine studies compared PC performance during different static stance conditions [29,32,41,43,44,[46][47][48]75]. Two studies failed to quantitatively compare conditions [32,43], while the seven remaining studies demonstrated significant differences between conditions, with more challenging stances causing increased instability [25,29,41,44,46,48,76].…”
Section: Discriminant Validity -Healthy Populationssupporting
confidence: 87%
“…The likely explanation for the popularity of this methodology is the lumbosacral regions proximity to the COM, with previous reports demonstrating that it closely matches the acceleration of the COM [66,67]. While seven studies investigated the use of multiple sensor mounting locations, only two studies with differing methodologies directly compared locations to determine which provided the most valuable measure of PC [13,25]. As such, the authors draw no conclusions pertaining to optimal sensor mounting location.…”
Section: Sensor Setup and Variablesmentioning
confidence: 97%
See 3 more Smart Citations